The Existence and Transformation of Bajo Sea Settlement Habitat in the Gulf of Bone - Syahriana Syam, Ananto Yudono, Ria Wikantari, Afifah Harisah (Design Engineering, 2021)
The existence of the Bajo tribe in the Gulf of Bone is attached to marine life dynamics which involves living freely as boat people in the ocean for centuries. They are also known as nomads but have settled in coastal areas over time. Therefore, this study aimed to examine the existence of the Bajo tribe and their transformation from living a nomadic life to settling in an area. This is a qualitative study which involves the exploration of field data, interviews with community leaders, and reviewing of previous research and the results showed the movement of the tribe from living in the sea to the Bone Bajo Gulf indicates a transformation of occupancy from water to land. This was based on the socio-cultural context, interactions with the Bugis, the construction of the Bajo ferry port, and the ecology of the waters which are observed to have affected the occupancy, the existence of marine culture, customs as well as livelihood orientation.